CAMPURAN BIJI NANGKA DAN MADU SEBAGAI MASKER WAJAH ANTI-AGING DI SURABAYA (Universitas PGRI Adi Buana Surabaya, 2024)
This research is motivated by the fact that beauty is coveted by every woman. Skin every day experience of environmental exposure to free radicals can be result to premature aging so expect no cosmetic preparation as an antidote to free radicals. The purpose is to describe the benefits and outcomes of care using a face mask jackfruit seeds and honey mixture with the independent variables are the face mask of a mixture of jackfruit seeds and honey as well as the dependent variable is reducing anti-aging on the face. Anti-aging is preparation to prevent the degenerative process. One appropriate action to right with the handling premature aging are use anti-aging products that contain vitamin C and E as well as having a high antioxidant to counteract free radicals contained in jackfruit seeds and honey. Data collection do administering a questionnaire, observation and experimentation, then the data were analyzed with descriptive methods, quantitative as well as with Anova formula to observe the condition of the skin, such as smoothness, brightness, firmness, and the condition of the spots of 25 mothers in Jl. Donowati RT.05 RW.01 Sukomanunggal sub-district, Surabaya. Anova test results obtainable F count> F-table so that H1 accepted which means that there is a difference / there is result mean the smoothness, brightness, firmness, and the condition of the spots after the use of masks jackfruit seeds and honey mixture.